Theological Education in Africa in the Post-1998 Lambeth Conference - Galgalo, Joseph D. (Journal of Anglican studies, 2008)
Since 1998 there has been a revived interest in theology among Anglicans around the world. Rowan Williams has encouraged this with the promotion of a Theological Education for the Anglican Communion Commission. The Global South primates have called for a rejection of the Western paradigm of Anglican theology in the context of the current debates about sexuality. The key Lambeth resolution on sexuality at the 1998 conference carries with it significant assumptions and challenges about theological method. There has been a renewed focus on context in doing theology. These changes can be seen in the case of Kenya where there has been a determined effort to re-cast the theological curriculum. Theology has also become more popular among lay people and theological work is expanding and flourishing.